Decreasing Trends in the Western US Dust Intensity With Rareness of Heavy Dust Events. Issue 13 (6th July 2022) - Aryal, Yog; Evans, Stuart
Abstract: Dust in the Western US (WUS) has impacts on many natural and human systems in the region. This study examines the temporal trends in dust event frequency and intensity and their correlations with local meteorology over the WUS. We use the observed daily near‐surface dust concentration during 2001–2020 from the Interagency Monitoring of Protected Visual Environments network. Low‐ and high‐concentration dust events are analyzed separately, and linear regression is used to estimate the trends and the correlations. Results show a significant decreasing trend in the occurrence frequency of spring and summer high‐concentration dust events, while the frequency of low‐concentration dust events shows significant increasing trends over the WUS. We examine weak and strong intensity categories and find that weak dust events generally have positive trends in their frequency of occurrence, and strong dust events have negative trends. The intensity of spring dust events has negative trends for both high‐concentration and low‐concentration dust events. Spring dust events are correlated with precipitation, and soil moisture over the Rockies and Southwest, while in the Great Plains (GP), dust events are correlated with precipitation. In the GP, the dust events are not correlated with soil moisture and the correlations with precipitation and wind speed are weak likely due to the anthropogenic dust sources. Compared to the spring, the trends in summer dust events and their correlations with meteorology are generally weak and inconsistent overall four regions. These results improve our understanding of current variability and the future of dust in the WUS. Plain Language Summary: The dry Western United States (WUS) is a prominent dust source region due to deserts, transient lakes, and dry farmlands. Dust occurrence in the WUS is highly seasonal and has strong temporal trends. Trends in dust occurrence can be due to changing the frequency or intensity of dust events or both. Using near‐surface dust concentration data from field stations across the WUS, we investigate changes in the spring and summer seasonal frequency of weak and intense dust events as well as their changing intensity. The intensity of both weak and intense dust events is decreasing over time, especially for intense dust events. The number of weak dust events is increasing, while the number of intense dust events is decreasing in recent years. The relationship between these trends and meteorology varies regionally. In the Rockies and Southwest, dust is strongly related to precipitation and soil moisture, while in the Great Plains, dust is related to precipitation and wind. Compared to the spring, the trends and the relationships for summer dust are weaker and vary from station to station. Key Points: Spring high‐concentration dust events are becoming less frequent, while the number of low‐concentration dust events is increasing The intensity of both low‐ and high‐concentration spring dust events is decreasing with a larger decrease in the high‐concentration regions Trends and variability in the dust events can be understood by trends and variability in the regional meteorology